Cau hoi: Xét đúng (sai) mệnh đề và phủ định mệnh đề sau : \(\forall x \in \mathbb{R}\) \({x^4} – {x^2} + 1 = \left( {{x^2} + \sqrt 3 x + 1} \right)\le

Photo of author

By Remi

Cau hoi: Xét đúng (sai) mệnh đề và phủ định mệnh đề sau : \(\forall x \in \mathbb{R}\) \({x^4} – {x^2} + 1 = \left( {{x^2} + \sqrt 3 x + 1} \right)\left( {{x^2} – \sqrt 3 x + 1} \right)\)
A. Mệnh đề \(\forall x \in \mathbb{R},\,\,{x^4} – {x^2} + 1 = \left( {{x^2} + \sqrt 3 x + 1} \right)\left( {{x^2} – \sqrt 3 x + 1} \right)\) đúng
Mệnh đề phủ định là \(\exists x \in \mathbb{R},\,\,{x^4} – {x^2} + 1 \ne \left( {{x^2} + \sqrt 3 x + 1} \right)\left( {{x^2} – \sqrt 3 x + 1} \right)\).
B. Mệnh đề \(\forall x \in \mathbb{R},\,\,{x^4} – {x^2} + 1 = \left( {{x^2} + \sqrt 3 x + 1} \right)\left( {{x^2} – \sqrt 3 x + 1} \right)\) đúng
Mệnh đề phủ định là \(x \in \mathbb{R},\,\,{x^4} – {x^2} + 1 \ne \left( {{x^2} + \sqrt 3 x + 1} \right)\left( {{x^2} – \sqrt 3 x + 1} \right)\).
C. Mệnh đề \(\forall x \in \mathbb{R},\,\,{x^4} – {x^2} + 1 = \left( {{x^2} + \sqrt 3 x + 1} \right)\left( {{x^2} – \sqrt 3 x + 1} \right)\) sai
Mệnh đề phủ định là \(\exists x \in \mathbb{R},\,\,{x^4} – {x^2} + 1 \ne \left( {{x^2} + \sqrt 3 x + 1} \right)\left( {{x^2} – \sqrt 3 x + 1} \right)\).
D. Mệnh đề \(\forall x \in \mathbb{R},\,\,{x^4} – {x^2} + 1 = \left( {{x^2} + \sqrt 3 x + 1} \right)\left( {{x^2} – \sqrt 3 x + 1} \right)\) sai
Mệnh đề phủ định là \(x \in \mathbb{R},\,\,{x^4} – {x^2} + 1 \ne \left( {{x^2} + \sqrt 3 x + 1} \right)\left( {{x^2} – \sqrt 3 x + 1} \right)\)




Viết một bình luận